Species Identification of Cannabis sativa Using Real‐Time Quantitative PCR (qPCR)1, 2. Issue 2 (13th February 2013) - Johnson, Christopher E.; Premasuthan, Amritha; Satkoski Trask, Jessica; Kanthaswamy, Sree
Abstract Most narcotics‐related cases in the United States involve Cannabis sativa. Material is typically identified based on the cystolithic hairs on the leaves and with chemical tests to identify of the presence of cannabinoids. Suspect seeds are germinated into a viable plant so that morphological and chemical tests can be conducted. Seed germination, however, causes undue analytical delays. DNA analyses that involve the chloroplast and nuclear genomes have been developed for identification of C. sativa materials, but they require several nanograms of template DNA. Using the trnL 3′ exon‐trnF intragenic spacer regions within the C. sativa chloroplast, we have developed a real‐time quantitative PCR assay that is capable of identifying picogram amounts of chloroplast DNA for species determination of suspected C. sativa material. This assay provides forensic science laboratories with a quick and reliable method to identify an unknown sample as C. sativa.